Influence of green solvent on levulinic acid production from lignocellulosic paper waste. (February 2020) - Dutta, Shanta; Yu, Iris K.M.; Tsang, Daniel C.W.; Su, Zhishan; Hu, Changwei; Wu, Kevin C.W.; Yip, Alex C.K.; Ok, Yong Sik; Poon, Chi Sun
Graphical abstract: Highlights: Green co-solvent systems enhanced cellulose depolymerization and product yield. Maximum 32% of levulinic acid (LA) yielded in GVL/H2 O solvent at 200 °C. GVL/H2 O system maintained high availability of soluble sugars. Acetone/H2 O solvent generated 17 Cmol% of LA at a lower temperature (180 °C) Higher temperature induced polymerization of sugars in acetone/H2 O solvent. Abstract: Lignocellulosic wastes constitute a significant portion of the municipal solid waste, which should be valorised for the synthesis of value-added chemicals to achieve circular bioeconomy. This study evaluates the use of γ-valerolactone (GVL) and acetone as green co-solvents to produce levulinic acid (LA) from lignocellulosic paper towel waste at different temperatures using dilute H2 SO4 . At the highest reaction temperature (200 °C), H2 O-only system achieved 15 Cmol% of LA at maximum. while GVL/H2 O and acetone/H2 O co-solvent systems enhanced the depolymerisation of paper towel waste and the subsequent conversion to LA, with the highest yield amounted to 32 Cmol%. Acetone/H2 O solvent system generated 17 Cmol% LA at a lower temperature (180 °C), while higher temperature induced polymerisation of soluble sugars and intermediates, hindering further conversion to LA. In contrast, the availability of soluble sugars was higher in the GVL/H2 O system, which favoured the production of LA at higher temperatures.